2018
DOI: 10.1016/j.jacc.2018.02.071
|View full text |Cite
|
Sign up to set email alerts
|

B-Type Natriuretic Peptide Levels and Mortality in Patients With and Without Heart Failure

Abstract: Among patients without HF, plasma BNP level is a stronger predictor of death than traditional risk factors. The risk for death associated with any given BNP level is similar between patients with and those without HF, particularly in the acute care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 35 publications
3
79
0
8
Order By: Relevance
“…This indication is supported by several diagnostic and randomised controlled studies and is consistently recommended in clinical practice guidelines . NPs also can help in a broad range of other indications, including prognostication of patients with established cardiovascular disorders such as myocardial infarction, valvular heart disease, HF and pulmonary embolism . Overall, BNP and NT‐proBNP have comparable diagnostic and prognostic accuracy; other NPs such as atrial natriuretic peptide (ANP) [or midregional proANP (MR‐proANP)] are also comparable, but less well documented.…”
Section: Introductionmentioning
confidence: 99%
“…This indication is supported by several diagnostic and randomised controlled studies and is consistently recommended in clinical practice guidelines . NPs also can help in a broad range of other indications, including prognostication of patients with established cardiovascular disorders such as myocardial infarction, valvular heart disease, HF and pulmonary embolism . Overall, BNP and NT‐proBNP have comparable diagnostic and prognostic accuracy; other NPs such as atrial natriuretic peptide (ANP) [or midregional proANP (MR‐proANP)] are also comparable, but less well documented.…”
Section: Introductionmentioning
confidence: 99%
“…Our unique dataset allow us to clarify clearly in a well characterised cohort of patients that a raised NT-pro-BNP is a marker of adverse prognosis even in people without LVSD as previously described. [14] Our data highlight that despite contemporary medical therapy coordinated by a secondary care clinic with a high rate of optimal doses, [48] the prognosis for consecutive, unselected elderly patients with HFrEF remains poor.…”
Section: Prognostic Utility Of a Raised Npmentioning
confidence: 84%
“…Elevated B-type natriuretic peptide (BNP) concentrations are associated with an adverse prognosis in the general population, [7] [8] and in people with [9][10] [11] and without [12][13] [14] LVSD and in heart failure, a reduction in NP concentrations with treatment is associated with an improvement in prognosis. [15] A series of screening studies in higher risk people have demonstrated that those with elevated BNP levels have a higher rate of LVSD.…”
Section: Introductionmentioning
confidence: 99%
“…Ranking of the percentage contribution of log 2 NT-proBNP and other variables in the final model was calculated using the following formula: (the χ 2 score of the predictor variable/the global χ 2 score) × 100. If an attenuation in the ranking of the percentage contribution of NT-proBNP compared with other variables was detected within any of the BMI and eGFR categories, the incremental value of NT-proBNP levels for incident HF was evaluated with Harrell's C-statistic for that model (52,53). First, we ran a Cox regression model with all the covariates except log 2 NT-proBNP and noted the C-statistic.…”
Section: Methodsmentioning
confidence: 99%